PENGARUH MOTIVASI, KOMUNIKASI, DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT PLN (PERSERO) ULP LONG IKIS - Pamungkas, Yoga; Hasan, Syahril; yuliani, tutik (MEDIA RISET EKONOMI [MR.EKO], 2026)
This study aims to explore the influence of Motivation, Communication, and Work Discipline on Employee Job Satisfaction. Using a quantitative approach, with purposive sampling as the sampling technique. The research sample consisted of PT PLN (Persero) ULP Long Ikis employees who met certain criteria, with a total of 40 people. A questionnaire was distributed as part of the data collection strategy. Multiple linear regression analysis was used in this investigation, and SmartPLS assisted in data processing. The results of the study indicate that motivation, communication, and work discipline all have a positive and significant influence on employee job satisfaction.